The Measurement and Behavior of Uncertainty: Evidence from the ECB Survey of Professional Forecasters. (12th January 2015) - Abel, Joshua; Rich, Robert; Song, Joseph; Tracy, Joseph
Summary: We examine matched point and density forecasts of output growth, inflation and unemployment from the ECB Survey of Professional Forecasters. We construct measures of uncertainty from individual histograms, and find that the measures display countercyclical behavior and have increased across all forecast horizons since 2007. We also derive measures of forecast dispersion and forecast accuracy, and find that they are not reliable proxies for uncertainty. There is, however, evidence of a meaningful co‐movement between uncertainty and aggregate point predictions for output growth and unemployment. These results are robust to changes in the composition of the survey respondents over time. Copyright © 2015 John Wiley & Sons, Ltd.